Aluminum alloy material for new energy automobile as well as preparation method and application of aluminum alloy material
By introducing trace amounts of La into the aluminum alloy materials of new energy vehicles and precisely controlling elements such as Si and Mg, and controlling Cu and Mn ratios, the technical bottlenecks in the coordinated optimization of strength and plasticity of aluminum alloy materials have been solved, and high-strength, high-plasticity and low-cost aluminum alloy materials are achieved, which is suitable for new energy vehicle battery packs.
Patent Information
- Application Number
- CN202510952579.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-10
- Publication Date
- 2025-08-29
AI Technical Summary
The existing aluminum alloy materials for new energy vehicles are difficult to meet the needs of high-energy density batteries, intelligent driving and extreme working conditions in the coordinated optimization of strength and plasticity. Especially in the molding of complex structural parts of the battery pack, crack defects are prone to occur, and the cost is high.
By introducing trace rare earth element La to refine the grains, accurately control the mass percentage of main elements such as Si and Mg, and at the same time adjusting the ratio of Cu and Mn, an aluminum alloy material with tensile strength ≥300MPa, yield strength ≥270MPa, and elongation after breaking ≥10%.
It has achieved the improvement of the comprehensive performance of aluminum alloy materials, reduced costs, and met the multiple needs of new energy vehicles for lightweight, high safety and molding and processing performance.
Smart Images

Figure BDA0005493213550000091 
Figure BDA0005493213550000101 
Figure BDA0005493213550000102
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of aluminum alloy materials, and specifically relates to an aluminum alloy material for new energy vehicles, a preparation method thereof, and applications thereof. Background Art
[0002] In recent years, as the core direction of the global automotive industry's transformation, new energy vehicles have continued to improve their technological iteration and market penetration. In order to achieve the "dual carbon" goals and improve driving range, lightweight design has become a key path for the research and development of new energy vehicles. Aluminum alloys have been widely used in key parts such as body frames, battery pack shells, and chassis structures of new energy vehicles because their density is only 1 / 3 of that of steel and they have good corrosion resistance and machinability. However, as new energy vehicles develop towards high-energy-density batteries, intelligent driving, and adaptability to extreme working conditions, higher requirements are placed on the mechanical properties of aluminum alloy materials: not only do they require sufficient tensile strength and yield strength to withstand complex loads, but they must also have good elongation after fracture to meet the requirements of forming processes such as stamping and welding. The comprehensive performance of existing aluminum alloy materials is still difficult to fully match the above requirements.
[0003] Currently, the aluminum alloy materials commonly used in the new energy vehicle field mainly include 6-series (Al-Mg-Si) and 5-series (Al-Mg) alloys. Among them, although the 6-series aluminum alloy improves its strength through the Mg2Si strengthening phase, its elongation after fracture is generally difficult to meet the requirements. During the forming process of complex structural parts of the battery pack (such as multi-pass stamping or complex surface processing), crack defects are easily generated. As a result, the material cannot meet the battery pack's requirements for structural part forming reliability and processing stability, limiting its application in battery pack components. 5-series aluminum alloys are mainly strengthened by Mg element solid solution, and have excellent plasticity (elongation after fracture is approximately 10% to 12%), but the tensile strength is generally only 250MPa to 280MPa, which cannot meet the strength requirements of high-load components (such as the battery pack lower shell). In addition, some improved aluminum alloys increase strength by adding elements such as Cu and Mn, but due to lax control of impurity elements, the toughness of the material decreases; or due to the improper addition ratio of rare earth elements, grain coarsening cannot be effectively suppressed, further exacerbating the contradiction between strength and plasticity.
[0004] In view of the technical bottleneck of the coordinated optimization of strength and plasticity of existing aluminum alloy materials used in new energy vehicle battery packs, it is necessary to develop an aluminum alloy material with better comprehensive performance to meet the multiple demands of new energy vehicles for lightweight structural parts in terms of strength, formability and safety. Summary of the Invention
[0005] Based on this, the present invention introduces trace rare earth elements La to refine the grains, accurately controls the mass percentages of main elements such as Si and Mg, and simultaneously regulates the ratio of Cu and Mn, so that the material can achieve synergistic improvements in key properties such as tensile strength, yield strength and elongation after fracture, thereby meeting the multiple requirements of new energy vehicles for lightweight, high safety and forming processing performance.
[0006] In order to achieve the above object, the present invention can adopt the following technical solutions:
[0007] On one hand, the present invention provides an aluminum alloy material for new energy vehicles, which includes the following components in percentage by mass: Si 0.62% to 0.68%, Fe≤0.19%, Cu 0.17% to 0.22%, Mn 0.1% to 0.15%, Mg 0.88% to 0.93%, Cr 0.08% to 0.15%, Zn≤0.2%, Ti≤0.15%, La 0.05% to 0.1%, unavoidable impurities total ≤0.1%, and the balance is Al.
[0008] Preferably, the aluminum alloy material for new energy vehicles meets one or more of the following conditions:
[0009] (a1) the mass percentage of Si is 0.64% to 0.66%, and the mass percentage of Mg is 0.89% to 0.91%;
[0010] (a2) the mass percentage of Cu is 0.19% to 0.21%, and the mass percentage of Mn is 0.12% to 0.14%;
[0011] (a3) The mass percentage of La is 0.06% to 0.08%.
[0012] Preferably, the aluminum alloy material for new energy vehicles can be selected from any one of the following:
[0013] (b1) comprising the following components in percentage by mass: Si 0.65%, Fe 0.1%, Cu 0.2%, Mn 0.12%, Mg 0.9%, Cr 0.11%, Zn 0.1%, Ti 0.07%, La 0.07%, unavoidable impurities ≤ 0.1% in total, and the balance Al;
[0014] (b2) comprising the following components in percentage by mass: Si 0.65%, Fe 0.1%, Cu 0.2%, Mn 0.1%, Mg 0.9%, Cr 0.11%, Zn 0.1%, Ti 0.07%, La 0.05%, unavoidable impurities totaling ≤ 0.1%, and the balance being Al;
[0015] (b3) comprising the following components in percentage by mass: Si 0.65%, Fe 0.1%, Cu 0.2%, Mn 0.15%, Mg 0.9%, Cr 0.11%, Zn 0.1%, Ti 0.07%, La 0.1%, unavoidable impurities ≤ 0.1% in total, and the balance Al;
[0016] (b4) comprising the following components in percentage by mass: Si 0.65%, Fe 0.1%, Cu 0.2%, Mn 0.1%, Mg 0.9%, Cr 0.11%, Zn 0.1%, Ti 0.07%, La 0.1%, unavoidable impurities ≤ 0.1% in total, and the balance Al;
[0017] (b5) comprising the following components in percentage by mass: Si 0.65%, Fe 0.1%, Cu 0.2%, Mn 0.15%, Mg 0.9%, Cr 0.11%, Zn 0.1%, Ti 0.07%, La 0.05%, unavoidable impurities ≤ 0.1% in total, balance Al;
[0018] (b6) comprising the following components in percentage by mass: Si 0.65%, Fe 0.1%, Cu 0.17%, Mn 0.12%, Mg 0.9%, Cr 0.11%, Zn 0.1%, Ti 0.07%, La 0.07%, unavoidable impurities totaling ≤ 0.1%, and the balance being Al;
[0019] (b7) comprising the following components in percentage by mass: Si 0.62%, Fe 0.1%, Cu 0.2%, Mn 0.12%, Mg 0.93%, Cr 0.11%, Zn 0.1%, Ti 0.07%, La 0.07%, unavoidable impurities totaling ≤ 0.1%, and the balance being Al;
[0020] (b8) comprising the following components in percentage by mass: Si 0.68%, Fe 0.1%, Cu 0.2%, Mn 0.12%, Mg 0.88%, Cr 0.11%, Zn 0.1%, Ti 0.07%, La 0.07%, unavoidable impurities ≤ 0.1% in total, balance Al;
[0021] (b9) comprising the following components in percentage by mass: Si 0.64%, Fe 0.1%, Cu 0.17%, Mn 0.15%, Mg 0.89%, Cr 0.1%, Zn 0.15%, Ti 0.1%, La 0.1%, unavoidable impurities totaling ≤ 0.1%, and the balance being Al;
[0022] (b10) comprises the following components in percentage by mass: Si 0.63%, Fe 0.15%, Cu 0.19%, Mn 0.15%, Mg 0.92%, Cr 0.1%, Zn 0.2%, Ti 0.13%, La 0.05%, unavoidable impurities totaling ≤0.1%, and the balance being Al.
[0023] Preferably, the aluminum alloy material for new energy vehicles has a tensile strength of ≥300 MPa, a yield strength of ≥270 MPa, and an elongation after fracture of ≥10%.
[0024] More preferably, the aluminum alloy material for new energy vehicles has a tensile strength of 300 MPa to 320 MPa, a yield strength of 270 MPa to 290 MPa, and an elongation after break of 10% to 12%.
[0025] Another aspect of the present invention provides a method for preparing the aluminum alloy material for new energy vehicles, the preparation method comprising:
[0026] (1) preparing ingredients according to the recipe to obtain raw materials;
[0027] (2) melting, refining, and casting the raw materials to obtain aluminum alloy rods;
[0028] (3) homogenizing the aluminum alloy rod;
[0029] (4) heating, cutting, extruding, cooling, and sawing the aluminum alloy rod to obtain aluminum profiles;
[0030] (5) Performing aging treatment on the aluminum profile to obtain the aluminum alloy material.
[0031] Preferably, in the above preparation method, in step (2):
[0032] Melting temperature is 710℃~760℃; and / or
[0033] The refining temperature is 700°C to 730°C and the refining time is 15min to 25min; and / or
[0034] The casting temperature is 690°C to 720°C, and the casting speed is 60mm / min to 80mm / min.
[0035] Preferably, in the above preparation method,
[0036] In step (3): the homogenization temperature is 540°C to 600°C, and the holding time is 6h to 11h; and / or
[0037] In step (5): the aging temperature is 180°C to 200°C, and the aging time is 5h to 12h.
[0038] Preferably, in the above preparation method, in step (4):
[0039] The heating temperature is 430°C to 500°C; and / or
[0040] Extrusion speed is 1m / min to 7m / min; and / or
[0041] Extrusion outlet temperature ≥ 520°C; and / or
[0042] The cooling method is selected from air cooling, mist cooling, water cooling, and / or
[0043] The cooling speed is less than 2 minutes to 100°C.
[0044] In another aspect, the present invention provides a battery pack for new energy vehicles, which includes the above-mentioned aluminum alloy material.
[0045] The beneficial effects of the present invention include:
[0046] (1) The aluminum alloy material for new energy vehicles provided by the present invention improves the mechanical properties by regulating the amount of Mn and La, and the amount of La and Mn is lower than that of the prior art (such as patent CN119144879A), which reduces the cost.
[0047] (2) The aluminum alloy material for new energy vehicles provided by the present invention can significantly reduce the cost by reducing the mass percentage of Cu to 0.17% to 0.22% by adding Mn and La and carefully controlling the formula; specifically, the mass percentage of Cu in the existing aluminum alloy material is 0.3% to 0.4%, while the price of copper is 80,000 yuan / ton, and the average unit price of Mn and La is 17,000 yuan / ton, which greatly reduces the cost.
[0048] (3) The present invention introduces a trace amount of rare earth element La to refine the grains, accurately controls the mass percentage of main elements such as Si and Mg, and regulates the ratio of Cu and Mn, so that the tensile strength of the prepared aluminum alloy material for new energy vehicles can reach 300MPa~320MPa, the yield strength can reach 270MPa~290MPa, and the elongation after fracture can reach 10%~12%. DETAILED DESCRIPTION
[0049] The examples are provided to better illustrate the present invention, but are not intended to limit the present invention to the examples. Therefore, non-essential improvements and adjustments to the embodiments made by those skilled in the art based on the above-mentioned invention still fall within the scope of protection of the present invention.
[0050] Unless otherwise defined, all technical and / or scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the invention pertains. It should be understood that certain features of the present invention (described in the context of separate embodiments for clarity) may also be provided in combination in a single embodiment. On the contrary, a plurality of features of the present invention (described in the context of a single embodiment for brevity) may also be provided separately or in any suitable combination or in any other described embodiment of the present invention when appropriate. Certain features described in the context of various embodiments will not be considered as essential features of those embodiments unless the embodiment is inoperable without those elements. The present invention will be further described below by specific examples, but it should be noted that the specific process conditions and results described in the embodiments of the present invention are only used to illustrate the present invention and cannot limit the scope of protection of the present invention. All equivalent changes or modifications made in accordance with the spirit and substance of the present invention should be included within the scope of protection of the present invention.
[0051] At present, the aluminum alloy materials commonly used in the field of new energy vehicles mainly include 6 series (Al~Mg~Si) and 5 series (Al~Mg) alloys. Although the 6 series aluminum alloy has improved its strength through the Mg2Si strengthening phase, its elongation after fracture is usually less than 8%. It is easy to produce crack defects during the forming process of complex structural parts of the battery pack (such as multi-pass stamping or complex surface processing), making it difficult for the material to meet the battery pack's requirements for structural part forming reliability and processing stability, limiting its application in battery pack components. In addition, some improved aluminum alloys increase their strength by adding elements such as Cu and Mn, but the toughness of the material decreases due to lax control of impurity elements; or due to the improper addition ratio of rare earth elements, it is unable to effectively suppress grain coarsening, further exacerbating the contradiction between strength and plasticity.
[0052] In order to solve the above problems, the present invention can adopt the following technical solutions:
[0053] In a first aspect, an embodiment of the present invention provides an aluminum alloy material for new energy vehicles, which includes the following components in percentage by mass: Si 0.62% to 0.68%, Fe≤0.19%, Cu 0.17% to 0.22%, Mn 0.1% to 0.15%, Mg 0.88% to 0.93%, Cr 0.08% to 0.15%, Zn≤0.2%, Ti≤0.15%, La 0.05% to 0.1%, unavoidable impurities total ≤0.1%, and the balance is Al.
[0054] It should be noted that the aluminum alloy material for new energy vehicles in the present invention is modified from aluminum alloy 6061. By introducing a trace amount of the rare earth element La to refine the grains, precisely controlling the mass percentages of major elements such as Si and Mg, and regulating the ratio of Cu and Mn, the aluminum alloy material's performance is improved, resulting in a tensile strength of 300-320 MPa, a yield strength of 270-290 MPa, and an elongation of 10-12%. Specifically, Si and Mg form a dispersed Mg2Si strengthening phase, while Cu precipitates an Al2Cu phase. These two phases, through precipitation strengthening, hinder dislocation motion, laying the foundation for high strength. The high Mg content dissolves in the Al matrix, causing lattice distortion and further enhancing matrix strength through solid solution strengthening. In addition, by regulating the amount of Mn and La, La and Mn work synergistically, thereby improving the mechanical properties. Compared with the existing technology (such as patent CN119144879A), the amount of La is lower, thereby reducing costs. In addition, by controlling Mn and La and carefully controlling the formula, the mass percentage of Cu is reduced to 0.17% to 0.22%, which can also significantly reduce costs. Specifically, the mass percentage of Cu in existing aluminum alloy materials is 0.3% to 0.4%, while the price of copper is 80,000 yuan / ton, and the average unit price of Mn and La is 17,000 yuan / ton, which greatly reduces costs.
[0055] In some specific examples, the aluminum alloy material for new energy vehicles meets one or more of the following conditions:
[0056] (a1) the mass percentage of Si is 0.64% to 0.66%, and the mass percentage of Mg is 0.89% to 0.91%;
[0057] (a2) the mass percentage of Cu is 0.19% to 0.21%, and the mass percentage of Mn is 0.12% to 0.14%;
[0058] (a3) The mass percentage of La is 0.06% to 0.08%.
[0059] It should be noted that in the present invention, the mass percentages of Si, Mg, Cu, Mn, and La can be preferably adjusted according to the above conditions (a1) to (a3) to obtain an aluminum alloy material for new energy vehicles with excellent mechanical properties. Furthermore, conditions (a1) to (a3) may be satisfied at any one of these conditions, and more preferably, all of these conditions are satisfied simultaneously.
[0060] In some specific examples, the aluminum alloy material for new energy vehicles can be selected from any one of the following:
[0061] (b1) comprising the following components in percentage by mass: Si 0.65%, Fe 0.1%, Cu 0.2%, Mn 0.12%, Mg 0.9%, Cr 0.11%, Zn 0.1%, Ti 0.07%, La 0.07%, unavoidable impurities ≤ 0.1% in total, and the balance Al;
[0062] (b2) comprising the following components in percentage by mass: Si 0.65%, Fe 0.1%, Cu 0.2%, Mn 0.1%, Mg 0.9%, Cr 0.11%, Zn 0.1%, Ti 0.07%, La 0.05%, unavoidable impurities totaling ≤ 0.1%, and the balance being Al;
[0063] (b3) comprising the following components in percentage by mass: Si 0.65%, Fe 0.1%, Cu 0.2%, Mn 0.15%, Mg 0.9%, Cr 0.11%, Zn 0.1%, Ti 0.07%, La 0.1%, unavoidable impurities ≤ 0.1% in total, and the balance Al;
[0064] (b4) comprising the following components in percentage by mass: Si 0.65%, Fe 0.1%, Cu 0.2%, Mn 0.1%, Mg 0.9%, Cr 0.11%, Zn 0.1%, Ti 0.07%, La 0.1%, unavoidable impurities ≤ 0.1% in total, and the balance Al;
[0065] (b5) comprising the following components in percentage by mass: Si 0.65%, Fe 0.1%, Cu 0.2%, Mn 0.15%, Mg 0.9%, Cr 0.11%, Zn 0.1%, Ti 0.07%, La 0.05%, unavoidable impurities ≤ 0.1% in total, balance Al;
[0066] (b6) comprising the following components in percentage by mass: Si 0.65%, Fe 0.1%, Cu 0.17%, Mn 0.12%, Mg 0.9%, Cr 0.11%, Zn 0.1%, Ti 0.07%, La 0.07%, unavoidable impurities totaling ≤ 0.1%, and the balance being Al;
[0067] (b7) comprising the following components in percentage by mass: Si 0.62%, Fe 0.1%, Cu 0.2%, Mn 0.12%, Mg 0.93%, Cr 0.11%, Zn 0.1%, Ti 0.07%, La 0.07%, unavoidable impurities totaling ≤ 0.1%, and the balance being Al;
[0068] (b8) comprising the following components in percentage by mass: Si 0.68%, Fe 0.1%, Cu 0.2%, Mn 0.12%, Mg 0.88%, Cr 0.11%, Zn 0.1%, Ti 0.07%, La 0.07%, unavoidable impurities ≤ 0.1% in total, balance Al;
[0069] (b9) comprising the following components in percentage by mass: Si 0.64%, Fe 0.1%, Cu 0.17%, Mn 0.15%, Mg 0.89%, Cr 0.1%, Zn 0.15%, Ti 0.1%, La 0.1%, unavoidable impurities totaling ≤ 0.1%, and the balance being Al;
[0070] (b10) comprises the following components in percentage by mass: Si 0.63%, Fe 0.15%, Cu 0.19%, Mn 0.15%, Mg 0.92%, Cr 0.1%, Zn 0.2%, Ti 0.13%, La 0.05%, unavoidable impurities totaling ≤0.1%, and the balance being Al.
[0071] It should be noted that the tensile strength of the aluminum alloy materials for new energy vehicles listed above can be ≥300 MPa, the yield strength can be ≥270 MPa, and the elongation after fracture can be ≥10%.
[0072] In some specific examples, the tensile strength of the aluminum alloy material for new energy vehicles in the present invention can be 300MPa~320MPa (for example, 305MPa, 310MPa or 315MPa, etc.), the yield strength can be 270MPa~290MPa (for example, 275MPa, 280MPa or 285MPa, etc.), and the elongation after fracture can be 10%~12% (for example, 10.5%, 11% or 11.5%, etc.).
[0073] In a second aspect, an embodiment of the present invention provides a method for preparing the above-mentioned aluminum alloy material for new energy vehicles, the preparation method comprising:
[0074] (1) preparing ingredients according to the recipe to obtain raw materials;
[0075] (2) melting, refining, and casting the raw materials to obtain aluminum alloy rods;
[0076] (3) homogenizing the aluminum alloy rod;
[0077] (4) heating, cutting, extruding, cooling, and sawing the aluminum alloy rod to obtain aluminum profiles;
[0078] (5) Performing aging treatment on the aluminum profile to obtain the aluminum alloy material.
[0079] In some specific examples, in step (2) of the above preparation method:
[0080] The melting temperature is 710°C to 760°C, such as 720°C, 730°C, 740°C or 750°C; and / or
[0081] The refining temperature is 700° C. to 730° C., for example, 710° C., 715° C., 720° C., or 725° C., and the refining time is 15 min to 25 min, for example, 16 min, 17 min, 18 min, 19 min, 20 min, 21 min, 22 min, 23 min, or 24 min; and / or
[0082] The casting temperature is 690°C to 720°C, such as 695°C, 700°C, 705°C, 710°C or 715°C, and the casting speed is 60mm / min to 80mm / min, such as 65mm / min, 70mm / min, 75mm / min or 80mm / min.
[0083] In some specific examples, in step (3) of the above preparation method, the homogenization temperature is 540° C. to 600° C., and the holding time is 6 h to 11 h.
[0084] It should be understood that the purpose of homogenization is to eliminate intracrystalline segregation and casting stress to obtain a cast rod with uniform structure. In the present invention, the homogenization temperature can preferably be 540°C to 600°C, such as 550°C, 560°C, 570°C, or 575°C; and the holding time can preferably be 6 hours to 11 hours, such as 6.5 hours, 7 hours, 7.5 hours, 8 hours, 8.5 hours, 9 hours, or 9.5 hours.
[0085] In some specific examples, in step (4) of the above preparation method,
[0086] The heating temperature is 430°C to 500°C; and / or
[0087] Extrusion speed is 1m / min to 7m / min; and / or
[0088] Extrusion outlet temperature ≥ 520℃; and / or
[0089] The cooling method is selected from air cooling, mist cooling, water cooling, water cooling including large water cooling or water cooling, and / or
[0090] The cooling speed is less than 2 minutes to 100°C.
[0091] It should be noted that the temperature at which the aluminum alloy rod in the present invention is heated can be 430°C to 500°C, such as 450°C, 480°C or 490°C; in addition, the extrusion speed can be 1m / min to 7m / min, such as 3m / min, 5m / min or 6m / min; in addition, the outlet temperature after extrusion is generally ≥520°C, and can reach a maximum of 535°C; in addition, the cooling method can be selected according to conventional technology in the field, for example, air cooling, mist cooling, water cooling (water cooling includes large water cooling or water cooling); in addition, the cooling rate is less than 2 minutes for cooling to 100°C, such as 1 minute or 2 minutes.
[0092] In some specific examples, in step (5) of the above preparation method, the aging temperature is 180° C. to 200° C., and the aging time is 5 h to 12 h.
[0093] It should be understood that aging treatment is a key process step in aluminum alloy processing. Its main purpose is to precipitate the solute atoms (such as alloying elements such as magnesium and silicon) in the supersaturated solid solution in the extruded aluminum alloy semi-finished product by controlling the temperature and time, forming a fine dispersed strengthening phase (such as Mg2Si phase). These strengthening phases can effectively hinder dislocation movement, thereby significantly improving the strength, hardness and comprehensive mechanical properties of the aluminum alloy. At the same time, aging treatment can also stabilize the structure and size of the material, reduce internal stress, and make the final aluminum alloy product (aluminum alloy material for new energy vehicles) meet the strength requirements of automotive parts. Among them, the aging temperature can be preferably 180℃~200℃, such as 165℃, 168℃, 170℃, 172℃, 180℃, 183℃ or 185℃, etc., and the aging time can be preferably 5h~12h, such as 6h, 7h, 8h, 9h, 10h or 11h, etc.
[0094] In a third aspect, an embodiment of the present invention provides a battery pack for a new energy vehicle, which includes the above-mentioned aluminum alloy material.
[0095] It should be noted that the aluminum alloy material in the present invention has excellent mechanical properties and can be prepared into battery packs for new energy vehicles. The preparation method and structure of battery packs for new energy vehicles are well known in the art.
[0096] The present invention is described in detail below by way of specific examples. It should also be understood that the following examples are only used to specifically illustrate the present invention and are not to be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all fall within the scope of protection of the present invention. The specific process parameters and the like in the following examples are only examples within a suitable range, and those skilled in the art can make selections within a suitable range through the description herein, and are not to be limited to the specific numerical values exemplified below.
[0097] Preparation Example
[0098] Example 1
[0099] (1) Prepare raw materials in proportion; the raw material formula is calculated in mass percentage, as shown in Table 1 below:
[0100] Table 1 Raw material formula of Example 1
[0101] Components Mass percentage Si 0.65% Fe 0.1% Cu 0.2% Mn 0.12% Mg 0.9% Cr 0.11% Zn 0.1% Ti 0.07% La 0.07% Total unavoidable impurities 0.1% Al Remaining Al
[0102] (2) melting, refining, and casting the raw materials to obtain aluminum alloy rods; wherein the melting temperature is 750° C.; the refining temperature is 720° C.; the refining time is 20 min; the casting temperature is 700° C.; and the casting speed is 70 mm / min;
[0103] (3) homogenizing the aluminum alloy rod; wherein the homogenization temperature is 575°C and the temperature is kept for 8 hours;
[0104] (4) heating, cutting, extruding, cooling, and sawing the aluminum alloy rod to obtain an aluminum profile; wherein the heating temperature is 450°C, the extrusion speed is 5 m / min, the outlet temperature after extrusion is 520°C, the cooling method is mist cooling, and the cooling speed is such that the time to cool to 100°C is 2 minutes;
[0105] (5) The aluminum profile is subjected to aging treatment to obtain an aluminum alloy material (i.e., an aluminum alloy material for new energy vehicles); wherein the aging temperature is 190° C. and the aging time is 9 h.
[0106] Example 2
[0107] Example 2 is roughly the same as Example 1. The difference between Example 2 and Example 1 is that the raw material formula is different. The aluminum alloy finished product is prepared in the same way as Example 1. Among them, the raw material formula in Example 2 is calculated in mass percentage, as shown in Table 2 below.
[0108] Table 2 Raw material formula of Example 2
[0109] Components Mass percentage Si 0.65% Fe 0.1% Cu 0.2% Mn 0.1% Mg 0.9% Cr 0.11% Zn 0.1% Ti 0.07% La 0.05% Total unavoidable impurities 0.1% Al Remaining Al
[0110] Example 3
[0111] Example 3 is roughly the same as Example 1. The difference between Example 3 and Example 1 is that the raw material formula is different. The aluminum alloy finished product is prepared in the same way as Example 1. Among them, the raw material formula in Example 3 is calculated in mass percentage, as shown in Table 3 below.
[0112] Table 3 Raw material formula of Example 3
[0113]
[0114]
[0115] Example 4
[0116] Example 4 is roughly the same as Example 1. The difference between Example 4 and Example 1 is that the raw material formula is different. The aluminum alloy finished product is prepared in the same way as Example 1. Among them, the raw material formula in Example 4 is calculated in mass percentage, as shown in Table 4 below.
[0117] Table 4 Raw material formula of Example 4
[0118] Components Mass percentage Si 0.65% Fe 0.1% Cu 0.2% Mn 0.1% Mg 0.9% Cr 0.11% Zn 0.1% Ti 0.07% La 0.1% Total unavoidable impurities 0.1% Al Remaining Al
[0119] Example 5
[0120] Example 5 is roughly the same as Example 1. The difference between Example 5 and Example 1 is that the raw material formula is different. The aluminum alloy finished product is prepared in the same way as Example 1. Among them, the raw material formula in Example 5 is calculated in mass percentage, as shown in Table 5 below.
[0121] Table 5 Raw material formula of Example 5
[0122]
[0123]
[0124] Example 6
[0125] Example 6 is roughly the same as Example 1. The difference between Example 6 and Example 1 is that the raw material formula is different. The aluminum alloy finished product is prepared in the same way as Example 1. Among them, the raw material formula in Example 6 is calculated in mass percentage, as shown in Table 6 below.
[0126] Table 6 Raw material formula of Example 6
[0127] Components Mass percentage Si 0.65% Fe 0.1% Cu 0.17% Mn 0.12% Mg 0.9% Cr 0.11% Zn 0.1% Ti 0.07% La 0.07% Total unavoidable impurities 0.1% Al Remaining Al
[0128] Example 7
[0129] Example 7 is roughly the same as Example 1. The difference between Example 7 and Example 1 is that the raw material formula is different. The aluminum alloy finished product is prepared in the same way as Example 1. Among them, the raw material formula in Example 7 is calculated in mass percentage, as shown in Table 7 below.
[0130] Table 7 Raw material formula of Example 7
[0131] Components Mass percentage Si 0.62% Fe 0.1% Cu 0.2% Mn 0.12% Mg 0.93% Cr 0.11% Zn 0.1% Ti 0.07% La 0.07% Total unavoidable impurities 0.1% Al Remaining Al
[0132] Example 8
[0133] Example 8 is roughly the same as Example 1. The difference between Example 8 and Example 1 is that the raw material formula is different. The aluminum alloy finished product is prepared in the same way as Example 1. Among them, the raw material formula in Example 8 is calculated in mass percentage, as shown in Table 8 below.
[0134] Table 8 Raw material formula of Example 8
[0135]
[0136]
[0137] Example 9
[0138] Example 9 is roughly the same as Example 1. The difference between Example 10 and Example 1 is that the raw material formula is different. The aluminum alloy finished product is prepared in the same way as Example 1. Among them, the raw material formula in Example 10 is calculated in mass percentage, as shown in Table 9 below.
[0139] Table 9 Raw material formula of Example 9
[0140] Components Mass percentage Si 0.64% Fe 0.1% Cu 0.17% Mn 0.15% Mg 0.89% Cr 0.1% Zn 0.15% Ti 0.1% La 0.1% Total unavoidable impurities 0.1% Al Remaining Al
[0141] Example 10
[0142] Example 10 is roughly the same as Example 1. The difference between Example 10 and Example 1 is that the raw material formula is different. The aluminum alloy finished product is prepared in the same way as Example 1. Among them, the raw material formula in Example 10 is calculated in mass percentage, as shown in Table 10 below.
[0143] Table 10 Raw material formula of Example 10
[0144]
[0145]
[0146] Comparative Example 1
[0147] Comparative Example 1 is roughly the same as Example 1. The difference between Comparative Example 1 and Example 1 is that the raw material formula is different. The aluminum alloy finished product is prepared in the same manner as Example 1. Among them, the raw material formula in Comparative Example 1 is calculated in mass percentage, as shown in Table 11 below.
[0148] Table 11 Raw material formula of comparative example 1
[0149] Components Mass percentage Si 0.65% Fe 0.1% Cu 0.2% Mn 0.12% Mg 0.9% Cr 0.11% Zn 0.1% Ti 0.07% La 0 Total unavoidable impurities 0.1% Al Remaining Al
[0150] Comparative Example 2
[0151] Comparative Example 2 is roughly the same as Example 1. The difference between Comparative Example 2 and Example 1 is that the raw material formula is different, and the aluminum alloy finished product is prepared in the same manner as Example 1; among them, the raw material formula in Comparative Example 2 is calculated in mass percentage, as shown in Table 12 below.
[0152] Table 12 Raw material formula of comparative example 2
[0153] Components Mass percentage Si 0.65% Fe 0.1% Cu 0.2% Mn 0.08% Mg 0.9% Cr 0.11% Zn 0.1% Ti 0.07% La 0.12% Total unavoidable impurities 0.1% Al Remaining Al
[0154] Comparative Example 3
[0155] Comparative Example 3 is roughly the same as Example 1. The difference between Comparative Example 3 and Example 1 is that the raw material formula is different, and the aluminum alloy finished product is prepared in the same manner as Example 1; among them, the raw material formula in Comparative Example 3 is calculated in mass percentage, as shown in Table 13 below.
[0156] Table 13 Raw material formula of comparative example 3
[0157]
[0158]
[0159] Comparative Example 4
[0160] Comparative Example 4 is roughly the same as Example 1. The difference between Comparative Example 4 and Example 1 is that the raw material formula is different, and the aluminum alloy finished product is prepared in the same manner as Example 1; among them, the raw material formula in Comparative Example 4 is calculated in mass percentage, as shown in Table 14 below.
[0161] Table 14 Raw material formula of comparative example 4
[0162] Components Mass percentage Si 0.65% Fe 0.1% Cu 0.24% Mn 0.12% Mg 0.9% Cr 0.11% Zn 0.1% Ti 0.07% La 0.07% Total unavoidable impurities 0.1% Al Remaining Al
[0163] Comparative Example 5
[0164] Comparative Example 5 is roughly the same as Example 1. The difference between Comparative Example 5 and Example 1 is that the raw material formula is different, and the aluminum alloy finished product is prepared in the same manner as Example 1; among them, the raw material formula in Comparative Example 5 is calculated in mass percentage, as shown in Table 15 below.
[0165] Table 15 Raw material formula of comparative example 5
[0166]
[0167]
[0168] Comparative Example 6
[0169] Comparative Example 6 is roughly the same as Example 1. The difference between Comparative Example 6 and Example 1 is that the raw material formula is different, and the aluminum alloy finished product is prepared in the same manner as Example 1; among them, the raw material formula in Comparative Example 6 is calculated in mass percentage, as shown in Table 16 below.
[0170] Table 16 Raw material formula of comparative example 6
[0171] Components Mass percentage Si 0.7% Fe 0.1% Cu 0.2% Mn 0.12% Mg 0.86% Cr 0.11% Zn 0.1% Ti 0.07% La 0.07% Total unavoidable impurities 0.1% Al Remaining Al
[0172] Performance testing
[0173] Tensile strength: According to GB / T 228.1-2021 Part 1: Room temperature test method, the tensile strength of the finished aluminum alloy products of each embodiment and each comparative example was tested. The test results are shown in Table 17.
[0174] Yield strength: According to GB / T 228.1-2021 Part 1: Room temperature test method, the yield strength of the finished aluminum alloy products of each embodiment and each comparative example was tested. The test results are shown in Table 17.
[0175] Elongation after fracture: In accordance with GB / T 228.1-2021 Part 1: Room temperature test method, the elongation after fracture of the aluminum alloy products of each embodiment and each comparative example was tested. The test results are shown in Table 17.
[0176] The experimental data and analysis are shown in Table 17 below:
[0177] Table 17 Aluminum alloy properties of each embodiment and each comparative example
[0178] Group Tensile strength / MPa Yield strength / MPa Elongation after break / % Example 1 321 289 11.2 Example 2 312 281 10.8 Example 3 315 283 11.6 Example 4 313 284 11.4 Example 5 317 285 10.3 Example 6 311 279 12.1 Example 7 316 282 11.5 Example 8 312 285 10.6 Example 9 309 286 12.3 Example 10 311 279 11.5 Comparative Example 1 261 249 5.9 Comparative Example 2 265 261 10.6 Comparative Example 3 312 280 7.8 Comparative Example 4 319 287 9.2 Comparative Example 5 263 258 11.0 Comparative Example 6 265 262 11.5
[0179] From Table 17 above, we can see that:
[0180] First, by comparing the embodiment with the comparative example, it can be seen that:
[0181] The tensile strength of the finished aluminum alloy product prepared in the embodiment (i.e., the aluminum alloy material for new energy vehicles) can reach 300MPa~320MPa, the yield strength can reach 270MPa~290MPa, and the elongation after fracture can reach 10%~12%; while the tensile strength, yield strength and elongation after fracture of the finished aluminum alloy product prepared in comparative example 1 are significantly lower than those in the embodiment; the tensile strength, yield strength and elongation after fracture of the finished aluminum alloy products prepared in comparative examples 2 to 6 cannot maintain excellent performance at the same time. Although some tensile strength and yield strength are excellent, the elongation after fracture performance is poor; although some elongation after fracture is excellent, some tensile strength and yield strength performance are poor.
[0182] Secondly, by comparing Example 1 with Comparative Example 1, it can be seen that:
[0183] In Comparative Example 1, no La element was added (other conditions were the same), and the tensile strength, yield strength, and elongation after fracture in Example 1 were significantly improved compared with those in Comparative Example 1. This indicates that the La element can play a role in grain refinement and improve the mechanical properties (especially elongation after fracture) of the aluminum alloy material in the present invention.
[0184] Secondly, by comparing Example 1 with Comparative Examples 2 to 3, it can be seen that:
[0185] Comparison of the raw material ratios of Comparative Example 2 and Example 1 shows that: Comparative Example 2 reduces the mass percentage of Mn to 0.08% (lower than the mass percentage of Mn in the present invention (0.1% to 0.15%)), while increasing the mass percentage of La to 0.12% (higher than the mass percentage of La in the present invention (0.05% to 0.1%)). Performance comparison shows that: the elongation after fracture in Comparative Example 2 is slightly improved compared with Example 1, but the tensile strength and yield strength are significantly lower than those in Example 1;
[0186] Comparison of the raw material ratios of Comparative Example 3 and Example 1 shows that: Comparative Example 3 increases the mass percentage of Mn to 0.17% (higher than the mass percentage of Mn in the present invention (0.1% to 0.15%)), while reducing the mass percentage of La to 0.04% (lower than the mass percentage of La in the present invention (0.05% to 0.1%)). Performance comparison shows that: the tensile strength and tensile strength of Comparative Example 3 are slightly lower than those of Example 1, but the elongation after break of Comparative Example 3 is significantly lower than that of Example 1.
[0187] As described above, in the present invention, the mechanical properties of the aluminum alloy material can be controlled by regulating the mass percentages of Mn and La. When the mass percentage of Mn is in the range of 0.1% to 0.15% and the mass percentage of La is in the range of 0.05% to 0.1%, the prepared aluminum alloy material has excellent mechanical properties.
[0188] Third, by comparing Example 1 with Comparative Example 4, we can know that:
[0189] Comparison of the raw material ratios of Comparative Example 4 and Example 1 shows that: Comparative Example 4 increases the mass percentage of Cu to 0.24% (higher than the mass percentage of Cu in the present invention (0.17% to 0.22%)); Performance comparison shows that: the tensile strength and tensile strength in Comparative Example 4 are slightly lower than those in Example 1, but the elongation after fracture in Comparative Example 4 is significantly lower than that in Example 1. This shows that the present invention achieves the purpose of reducing the Cu content while also achieving excellent mechanical properties; at the same time, increasing the Cu content in the present invention will reduce the comprehensive mechanical properties of the prepared aluminum alloy, which indirectly shows that the Cu content range in the present invention makes it have a strong correlation with other elements in the present invention, and work together to improve the performance of the aluminum alloy material.
[0190] Fourthly, by comparing Example 1 with Comparative Examples 5 to 6, it can be seen that:
[0191] Comparison of the raw material ratios of Comparative Example 5 and Example 1 shows that: Comparative Example 5 reduces the mass percentage of Si to 0.6% (lower than the mass percentage of Si in the present invention (0.62% to 0.68%)), while increasing the mass percentage of Mg to 0.95% (higher than the mass percentage of Mg in the present invention (0.88% to 0.93%)); Performance comparison shows that: the elongation after fracture in Comparative Example 5 is not significantly different from that in Example 1, but the tensile strength and yield strength are significantly lower than those in Example 1;
[0192] Comparison of the raw material ratios of Comparative Example 6 and Example 1 shows that: Comparative Example 6 increases the mass percentage of Si to 0.7% (higher than the mass percentage of Si in the present invention (0.62% to 0.68%)), while reducing the mass percentage of Mg to 0.86% (lower than the mass percentage of Mg in the present invention (0.88% to 0.93%)); Performance comparison shows that: the elongation after fracture in Comparative Example 6 is slightly higher than that in Example 1, but the tensile strength and yield strength are significantly lower than those in Example 1;
[0193] The above data indicate that Si and Mg in the present invention also need to be maintained within a certain range so that the prepared aluminum alloy material can simultaneously have excellent tensile strength, yield strength and elongation after fracture.
[0194] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not limiting. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions of the present invention, which should all be covered by the scope of the claims of the present invention.
Claims
1. An aluminum alloy material for new energy vehicles, characterized in that: The steel comprises the following components in percentage by mass: Si 0.62% to 0.68%, Fe ≤ 0.19%, Cu 0.17% to 0.22%, Mn 0.1% to 0.15%, Mg 0.88% to 0.93%, Cr 0.08% to 0.15%, Zn ≤ 0.2%, Ti ≤ 0.15%, La 0.05% to 0.1%, unavoidable impurities ≤ 0.1% in total, and the balance is Al.
2. The aluminum alloy material for new energy vehicles according to claim 1, characterized in that: The aluminum alloy material meets one or more of the following conditions: (a1) the mass percentage of Si is 0.64% to 0.66%, and the mass percentage of Mg is 0.89% to 0.91%; (a2) the mass percentage of Cu is 0.19% to 0.21%, and the mass percentage of Mn is 0.12% to 0.14%; (a3) The mass percentage of La is 0.06% to 0.08%.
3. The aluminum alloy material for new energy vehicles according to claim 1, characterized in that: The aluminum alloy material is selected from any one of the following: (b1) comprising the following components in percentage by mass: Si 0.65%, Fe 0.1%, Cu 0.2%, Mn 0.12%, Mg 0.9%, Cr 0.11%, Zn 0.1%, Ti 0.07%, La 0.07%, unavoidable impurities ≤ 0.1% in total, and the balance Al; (b2) comprising the following components in percentage by mass: Si 0.65%, Fe 0.1%, Cu 0.2%, Mn 0.1%, Mg 0.9%, Cr 0.11%, Zn 0.1%, Ti 0.07%, La 0.05%, unavoidable impurities ≤ 0.1% in total, and the balance Al; (b3) comprising the following components in percentage by mass: Si 0.65%, Fe 0.1%, Cu 0.2%, Mn 0.15%, Mg 0.9%, Cr 0.11%, Zn 0.1%, Ti 0.07%, La 0.1%, unavoidable impurities ≤ 0.1% in total, and the balance Al; (b4) comprising the following components in percentage by mass: Si 0.65%, Fe 0.1%, Cu 0.2%, Mn 0.1%, Mg 0.9%, Cr 0.11%, Zn 0.1%, Ti 0.07%, La 0.1%, unavoidable impurities ≤ 0.1% in total, and the balance Al; (b5) comprising the following components in percentage by mass: Si 0.65%, Fe 0.1%, Cu 0.2%, Mn 0.15%, Mg 0.9%, Cr 0.11%, Zn 0.1%, Ti 0.07%, La 0.05%, unavoidable impurities ≤ 0.1% in total, and the balance Al; (b6) comprising the following components, calculated by mass percentage: Si 0.65%, Fe 0.1%, Cu 0.17%, Mn 0.12%, Mg 0.9%, Cr 0.11%, Zn 0.1%, Ti 0.07%, La 0.07%, unavoidable impurities ≤ 0.1% in total, and the balance Al; (b7) comprising the following components in percentage by mass: Si 0.62%, Fe 0.1%, Cu 0.2%, Mn 0.12%, Mg 0.93%, Cr 0.11%, Zn 0.1%, Ti 0.07%, La 0.07%, unavoidable impurities ≤ 0.1% in total, balance Al; (b8) comprising the following components in percentage by mass: Si 0.68%, Fe 0.1%, Cu 0.2%, Mn 0.12%, Mg 0.88%, Cr 0.11%, Zn 0.1%, Ti 0.07%, La 0.07%, unavoidable impurities ≤ 0.1% in total, balance Al; (b9) comprising the following components in percentage by mass: Si 0.64%, Fe 0.1%, Cu 0.17%, Mn 0.15%, Mg 0.89%, Cr 0.1%, Zn 0.15%, Ti 0.1%, La 0.1%, unavoidable impurities totaling ≤ 0.1%, and the balance being Al; (b10) comprises the following components in percentage by mass: Si 0.63%, Fe 0.15%, Cu 0.19%, Mn 0.15%, Mg 0.92%, Cr 0.1%, Zn 0.2%, Ti 0.13%, La 0.05%, unavoidable impurities totaling ≤0.1%, and the balance being Al.
4. The aluminum alloy material for new energy vehicles according to any one of claims 1 to 3, characterized in that: The aluminum alloy material has a tensile strength of ≥300 MPa, a yield strength of ≥270 MPa, and an elongation after fracture of ≥10%.
5. The aluminum alloy material for new energy vehicles according to claim 4, characterized in that: The aluminum alloy material for new energy vehicles has a tensile strength of 300 MPa to 320 MPa, a yield strength of 270 MPa to 290 MPa, and an elongation after fracture of 10% to 12%.
6. The method for preparing the aluminum alloy material for new energy vehicles according to any one of claims 1 to 5, characterized in that: The preparation method comprises: (1) preparing ingredients according to the recipe to obtain raw materials; (2) melting, refining, and casting the raw materials to obtain aluminum alloy rods; (3) homogenizing the aluminum alloy rod; (4) heating, cutting, extruding, cooling, and sawing the aluminum alloy rod to obtain aluminum profiles; (5) Performing aging treatment on the aluminum profile to obtain the aluminum alloy material.
7. The preparation method according to claim 6, characterized in that In step (2): Melting temperature is 710℃~760℃; and / or The refining temperature is 700°C to 730°C and the refining time is 15min to 25min; and / or The casting temperature is 690°C to 720°C, and the casting speed is 60mm / min to 80mm / min.
8. The preparation method according to claim 6 or 7, characterized in that In step (3): the homogenization temperature is 540°C to 600°C, and the holding time is 6h to 11h; and / or In step (5): the aging temperature is 180°C to 200°C, and the aging time is 5h to 12h.
9. The preparation method according to claim 6 or 7, characterized in that In step (4): The heating temperature is 430°C to 500°C; and / or Extrusion speed is 1m / min to 7m / min; and / or Extrusion outlet temperature ≥ 520℃; and / or Cooling methods include air cooling, mist cooling, water cooling, and / or The cooling speed is less than 2 minutes to 100°C.
10. A battery pack for new energy vehicles, characterized in that: The invention comprises the aluminum alloy material according to any one of claims 1 to 5 or the aluminum alloy material prepared by the preparation method according to claims 6 to 10.
Citation Information
Patent Citations
Aluminum alloy and preparation method thereof, box body for packaging battery, battery and electric device
CN119144879A